Survival and repair durability in patients undergoing concomitant aortic valve reimplantation and mitral valve repairCentral MessagePerspective - Daniel J.P. Burns, MD, MPhil; Jeevanantham Rajeswaran, PhD; Milind Y. Desai, MD; A. Marc Gillinov, MD; Kevin Hodges, MD; Eric E. Roselli, MD; Patrick R. Vargo, MD; Lars G. Svensson, MD, PhD (JTCVS Techniques)
Objective: The study objective was to determine repair durability and survival in patients with and without connective tissue disorders undergoing concomitant aortic valve reimplantation and mitral valve repair. Methods: From 2002 to 2019, 68 patients underwent concomitant aortic valve reimplantation and mitral valve repair, including 27 patients with Marfan syndrome (39.7%). Follow-up echocardiograms were analyzed using nonlinear multiphase mixed-effects cumulative logistic regression. The regurgitation grade over time was estimated by averaging patient-specific profiles. Survival and freedom from reoperation were estimated by the Kaplan–Meier method. Results: At 7 years, 11% of patients had aortic insufficiency greater than mild (severe in 2 patients). There was no difference in greater than mild aortic insufficiency between patients with or without Marfan syndrome (P = .37). Twenty percent of patients had progressed to mitral regurgitation greater than mild (severe in only 1 patient). The prevalence of recurrent mitral regurgitation was higher in those without Marfan syndrome, with greater than mild regurgitation increasing to 24% by 2 years and remaining constant thereafter (P = .04). Freedom from reoperation on the aortic valve or mitral valve was 83% at 10 years and did not differ between Marfan syndrome groups. There were no cases of perioperative mortality. Survival at 5 and 10 years was 94% and 87%, respectively, without a difference between those with and without Marfan syndrome. Conclusions: Patients can undergo a total repair strategy using combined aortic valve reimplantation and mitral valve repair procedures with a low risk of mortality and complications, with favorable freedom from both residual valve regurgitation and reoperation.